FATWA GREETINGS PLURALISTIK: KONTEKS TEOLOGI INKLUSIF DAN PLURALISME AGAMA DI INDONESIA KONTEMPORER - Achmad Riady (IAIN Ambon, 2025)
This study aims to analyze the discourse construction in the fatwa issued by the Indonesian Council of Ulama (Majelis Ulama Indonesia/MUI) regarding interreligious greetings and its relation to pluralism dynamics in Indonesia. Utilizing a qualitative approach with a literature-based method and critical discourse analysis (Fairclough model), the study explores the linguistic and semantic features of fatwa texts, as well as the embedded religious symbols and power relations. The findings reveal that fatwas not only function as normative religious authority but also shape social structures through the production of religious meanings. Public resistance, the emergence of alternative religious discourses in digital media, and the role of moderate religious organizations are pivotal in shaping social responses. Moreover, the maqashid shariah framework and progressive theology contribute to reconstructing the relationship between theological symbolism and social ethics in a plural society. This study highlights the need for inclusive fatwas that consider social diversity and universal human values.